Why are rights offers in Hong Kong so different? - Lee, Chin Chong; Poon, Wai Ching; Sinnakkannu, Jothee (Elsevier, 2014)
Investors react adversely to the announcements of rights offers in Hong Kong and the abnormal return of rights offers on the announcement day is −12.10%. After taking price discounts, underwriting fees and abnormal returns into consideration, the total direct and indirect costs of the seasoned issuers of rights offers are tremendously high. The cross-sectional analysis shows that investors react more adversely to the issuers of rights offers with lower growth prospects, higher free cash flows, larger issue scales, lower pre-issuance stock run up and higher debt capacity. Our empirical result also indicates that cash-rich firms with fewinvestment opportunities and firmswith poor quality in terms of lower market-to-book ratio and larger price discounts choose rights offers over private equity placements. All this evidence supports that agency costs and private benefits of control matter in equity financing.